Community Sports Program in a Vocational College in Jiangxi Province, China - Li, Xiang (International Journal of Social Sciences and Public Administration, 2024)
This study aimed to assess Jiangxi Science and Technology Vocational College students' perceptions of community sports programs with a view to developing improved community sports programs. The study found that students generally rated the program as excellent in terms of accessibility, sustainability, effectiveness and satisfaction, demonstrating its success in addressing barriers to participation, using environmentally friendly, inclusive and flexible strategies, and responding to student feedback responded positively. Although there were differences in terms of gender, age, course, and grade level, these factors had no significant impact on students' evaluations of community sports programs. Through the evaluation of existing programs and suggestions for improvement, this study hopes to provide a valuable reference for the development of sports programs in vocational colleges.